Reinterpretasi dalam Pertunjukan Teater Lenong Betawi - Deden Haerudin; Fachri Helmanto (PANGGUNG, 2025)
Urbanization and digitalization of culture in big cities including Jakarta, shift the way the younger generation interprets traditional symbols. Gatot Kaca, famous as a puppet character, also experienced reinterpretation through performing arts as a strategy for preserving cultural identity. This study aims to understand the reinterpretation in the Lenong Betawi performance of the play Satria Millennial, where Gatot Kaca is adapted into an urban expression space. Using a phenomenological approach, data was collected through interviews and documentation of the creative process of the Satria Millennial performance. Furthermore, the data obtained were analyzed thematically following Moustakas' framework. The results show three main reinterpretations: (1) a pandemic-themed story, (2) the character of Gatot Kaca transforming into a comic-educational figure, and (3) the performance integrating lenong, musical, and urban humor. These three reinterpretations strengthen the function of art as a vehicle for cultural preservation, education, and mediation of local cultural identity in modern society.